Atividade antimicrobiana e antibiofilme da fluoxetina contra cepas de Stenotrophomonas maltophilia isoladas de pacientes de um hospital pediátrico no Ceará - Dantas Júnior, Vicente Maciel (2024)
The irrational use of antimicrobials and the global shortage of new drugs intensify the threat posed by superbugs, in addition to being an onerous, bureaucratic and prolonged process, which does not bring the financial return expected by large pharmaceutical companies. In this context, drug repositioning is a viable alternative for the treatment of infections of important clinical impact, such as those caused by Stenotrophomonas maltophilia, especially in pediatrics. Thus, the study aimed to observe the incidence of these infections and their outcomes in the last 5 years in a pediatric hospital in Ceará and repositioned fluoxetine to describe its antimicrobial and antibiofilm properties against this microorganism. The data on infections, clinical outcomes, topography of infections, age and gender of patients were followed through reports issued by the hospital's information technology systems and segregated year by year for later analysis. 10 strains isolated from hospital patients were selected and the antimicrobial activity of fluoxetine was tested in planktonic and biofilm. Fluoxetine was associated with antimicrobials used to treat S. maltophilia infections to assess improvement or interference in parameters. The same was done with drugs of known resistance to evaluate changes in the pattern and possible inhibition of these mechanisms. During the study period, 303 cases of infection by the pathogen were confirmed in 213 patients and 93 (43.66%) died due to alternative treatment, since the first line was out of the market. Fluoxetine showed antimicrobial activity alone but interacted negatively with the response of other drugs (trimethoprim/sulfamethoxazole, levofloxacin, meropenem, and gentamicin) when combined. High mortality rates observed coincided with findings in other publications and reiterated prolonged hospitalizations and immunocompromise due to COVID-19 as a substantial risk factor. More robust research is suggested regarding the possibility of using fluoxetine in antibacterial treatment and observation of its interaction at the molecular level with other drugs and consequently compromising typical response.